A Technical Note on Australian Default Superannuation Investment Strategies - Loretta Iskra (Australasian Accounting, Business and Finance Journal, 2012)
Superannuation has become more complex over time. Individual investors are inclined to seek the ‘path of least resistance’ and invest in default investment funds which are typically concentrated in high risk assets. Understanding how these funds will meet the individual needs of members relative to their changing circumstances can provide peace of mind and confidence in the market. Given the value of superannuation as an investment in terms of the economy, it is paramount than an appropriate mechanism be in place for default fund investors. This paper will clarify the existing position relative to default fund investment options and outline future research which will provide the impetus for change in terms of government policy, the financial planning profession and for industry superannuation funds.
Keywords: era2015